The Way To Overcome Students’ Hesitation In Speaking English At The 10 Th Grade of Senior High School In Bekasi - Rumlus, Grediana (Syntax Literate, 2020)
English as an international language needs to be used in daily communication so that speakers are accustomed to using it. But the facts show that many people, especially class X students at one of the high schools in Bekasi, find it difficult to speak English for fear of being wrong. So this paper aims to find out the causes of difficulties for students to speak English. The author conducted research in 2 classes with 60 students. The first step is to hold a group discussion using an English textbook in the two classes. The second stage uses the control class and the experimental class. The control class still uses English textbooks as discussion material, while the control class watches 2 films in English and each group tells the contents of the film according to their understanding. Each group member in the experimental class tells the contents of the film very actively and enthusiastically, while the control class only talk by the group leader. The observations showed that audiovisual and learning techniques with stories were very significant in the experimental class students. It can be proven by the activity of each group member speaking. It was concluded that audiovisual and simple learning techniques were very enjoyable and increased the speaking activity in one of high school students at grade X in Bekasi. Keywords: Habit, watching/listening, fun